2008
DOI: 10.1254/jphs.08222fp
|View full text |Cite
|
Sign up to set email alerts
|

Repeated Pre-treatment With Antihistamines Causes Transcriptional Up-regulations of Histamine H1 Receptor and Interleukin-4 Genes in Toluene-2,4-diisocyanate–Sensitized Rats

Abstract: Abstract. Antihistamines are effective for treatment of seasonal nasal allergy. Recently, prophylactic treatment with antihistamines in patients with pollinosis was reported to be more effective when started before the pollen season. The administration with antihistamines from 2 to 6 weeks before onset of the pollen season is recommended for management of allergic rhinitis in Japan. To determine the reason for the effectiveness of prophylactic treatment with antihistamines, the effects of repeated pre-treatmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
33
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
3

Relationship

4
5

Authors

Journals

citations
Cited by 46 publications
(34 citation statements)
references
References 32 publications
1
33
0
Order By: Relevance
“…This hypothesis is supported by recent findings that prophylactic treatment with H 1 antihistamines suppressed the TDI-induced up-regulation of H1R and IL-4 mRNAs in TDI-sensitized rats (34). To explore this possibility, we applied rrIL-4 or histamine directly to FIGURE 2.…”
Section: Effect Of Il-4 or Histamine On Nasal Mucosal H1r Or Il-4 Mrnmentioning
confidence: 55%
See 1 more Smart Citation
“…This hypothesis is supported by recent findings that prophylactic treatment with H 1 antihistamines suppressed the TDI-induced up-regulation of H1R and IL-4 mRNAs in TDI-sensitized rats (34). To explore this possibility, we applied rrIL-4 or histamine directly to FIGURE 2.…”
Section: Effect Of Il-4 or Histamine On Nasal Mucosal H1r Or Il-4 Mrnmentioning
confidence: 55%
“…These findings suggest the existence of multiple, H1R-mediated and non-H1R-mediated pathways for H1R mRNA up-regulation. Recently, we reported that prophylactic treatment with H 1 antihistamines suppressed TDI-induced up-regulation of both H1R and IL-4 mRNAs in TDI-sensitized rats (34). Direct administration of IL-4 into the nasal cavity of non-TDI-treated normal rats up-regulated the expression of H1R mRNA (Fig.…”
Section: Discussionmentioning
confidence: 84%
“…We think IL-4 may be a candidate responsible for H1R mRNA up-regulation. We have reported that prophylactic treatment with H 1 -antihistamines suppressed TDI-induced up-regulations of both H1R and IL-4 mRNAs in TDI-sensitized rats (71). Direct administration of IL-4 into the nasal cavity of non-TDI-treated normal rats up-regulated the expression of H1R mRNA (unpublished result).…”
Section: Discussionmentioning
confidence: 81%
“…The strength of H1R signaling depends on the H1R expression level (8). Our recent studies have demonstrated that the level of H1R gene expression is strongly correlated with the severity of allergic symptoms in model rats and patients with pollinosis (9,10), and compounds that suppress H1R gene up-regulation alleviate allergic symptoms (11)(12)(13)(14)(15)(16). These findings suggest that the H1R gene is an allergy-sensitive gene, i.e.…”
mentioning
confidence: 98%